On One Generalization of the Hardy–Littlewood–Pólya Inequality - Belov, I. S. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We generalize the Hardy–Littlewood–Pólya inequality for numerical sets to certain sets of vectors on a plane.